The Use of Collaborative Design Thinking in Improving Student Writing Skill - Addawiyah, Karimah Robiatul (ELLITE, 2020)
Writing is still considered a difficult skill to master. Problems arise from variousaspects of writing namely grammar, vocabulary, types of text, outline, and soon. Tackling these problems is possible with appropriate teaching method. TheCollaborative Thinking Design Method (CoDeT) was chosen as an effectiveand innovative method to help students improve students’ writing skills as thisencouraes them to be active in the learning process and discuss with classmates.The purpose of this study was to determine whether there was a significantimprovement in the use of CoDeT method in students’ writing skills. Usingthe VII grade students of MTs AT-Tawazun Subang in year 2019/2020 aspopulation, this study used quantitative methods with experimental researchdesign. The average values obtained in the Pre- and post-test were 52.73 and91.92, respectively. This means that Tcount ttable or 4.01 3.06, with theresult that students’ writing skills are enhanced using Collaborative DesignThinking (CoDeT) method instead of the conventional method. This meansthat there is a significant improvement in the inclusion of Collaborative DesignThinking (CoDeT) method on students’ writing skills. It implies that CoDeTmethod can enhance students’ ability to teach writing skills in narrative texts.Through this research, several advantages of using the Collaborative DesignThinking (CoDeT) method in teaching writing skills to seventh grade studentswere revealed, such as 1). encouraging students to be actively involved in thelearning process and 2). facilitating students in understanding teaching materialthrough discussion.